Inteligencia emocional y actitud hacia el proyecto educativo institucional de los docentes de las instituciones educativas del distrito de Huaura - Retto M., Jesús (2014)
Emotional Intelligence of a Probabilistic sample of 150 teachers from the Huaura district (Department of Lima) is contrasted with their attitudes toward the Institutional Educational Project of their schools in order to detect if there is a link between these two variables. At the same time, one investigates what kind of attitudes are the ones which have numeric predominance. This is a research with Quantitative approach, Correlacional scope, and Non Experimental design of Transeccional type. To size variables we applied the Emotional Intelligence Scale adapted from Ruiz, 2004; and the Attitudes Scale concerning the Institu- tional Educational Project. The statistical results let us conclude that such variables are not correlated between them, and that acceptation is the attitude with prevalence.